TINJAUAN ASPEK KEAMANAN DAN KERAHASIAAN BERKAS REKAM MEDIS DI RSUD EMPAT LAWANG SUMATRA SELATAN - Septia; Irine Diana Sari Wijayanti (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2024)
The aim to be achieved is to determine the security of medical record files, the confidentiality of medical record files at Empat Lawang Regional Hospital, South Sumatra, to find out the obstacles and solutions to overcome obstacles in maintaining the security and confidentiality of medical record files at Empat Lawang Regional Hospital, South Sumatra. This type of writing uses qualitative writing, with three sources, data collection techniques through interviews, observation, documentation, literature study), which are then processed first before they are ready for use, and then analyzed using Miles and Huberman's qualitative analysis. The result is the security of medical record documents at the Empat Lawang Regional Hospital, South Sumatra, where there is an SOP which serves as a guideline for maintaining the security of medical records. Apart from that, fire extinguishers are available to anticipate if a fire occurs. Meanwhile, in terms of quality, this is done by keeping the room temperature under control, thereby avoiding insects and fungi which can damage medical records. A special medical records room was also created. Confidentiality of medical record documents at Empat Lawang Regional Hospital, South Sumatra, there is an SOP that regulates the confidentiality of medical record documents. Apart from that, this document can only be accessed by certain parties, so there is a rule that only medical records employees can enter the room. In the system there are also expeditions and loan books, so that the entry and exit of medical record documents remains controlled. The medical records room is also equipped with a Pingerkey or ID Card and CCTV to optimize the confidentiality of this medical records room. The obstacle in maintaining the security and confidentiality of medical record files at Empat Lawang Regional Hospital, South Sumatra is that the door is always open and not locked, so that non-medical record officers can enter without permission, apart from that there are several officers who are still eating and drinking in the room. The solution is that the front door should be repaired and a warning board provided such as "Staff Only", this is to avoid things that could cause other officers to enter without permission.